Hydrogen Peroxide and Hypochlorite Responsive Fluorescent Nanoprobes for Sensitive Cancer Cell Imaging - Yun Chen; Jing Ye; Gang Lv; Weiwei Liu; Hui Jiang; Xiaohui Liu; Xuemei Wang (Biosensors, 2022)
Accurate diagnosis of cancer cells directly affects the clinical treatment of cancer and can significantly improve the therapeutic effect of cancer patients. Cancer cells have a unique microenvironment with a large amount of peroxide inside, effectively differentiated from relevant microenvironment normal cells. Therefore, designing the high-sensitive probes to recognize and distinguish the special physiological microenvironment of cancer cells can shed light on the early diagnosis of cancers. In this article, we design and construct a fluorescence (FL) contrast agent for cancer cell recognition and imaging analysis. Firstly, luminol-gold NPs (Lum-AuNPs) have been initially built, and then successfully loaded with the fluorescent receptor Chlorin e6 (Ce6) to prepare the luminescent nanoprobes (Ce6@Lum-AuNPs) with green synthesis, i.e., with biocompatible agents and mild temperature. The as-prepared fluorescent Ce6@Lum-AuNPs can efficiently and sensitively realize FL bioimaging of cancer cells. The relevant bio-sensing mechanism pertains to the presence of hypochlorite (ClO−); hydrogen peroxide (H2O2) in cancer cells could readily interact with luminol to produce chemiluminescence, which can activate the Ce6 component to emit near-infrared (NIR) FL. Therefore, this raises the possibility of utilizing the Ce6@Lum-AuNPs as efficient fluorescent nanoprobes for promising cancer early diagnosis and other relevant disease bioanalysis.